Molecular insights into the transformation of dissolved organic matter during hyperthermophilic composting using ESI FT-ICR MS. (November 2019) - Yu, Zhen; Liu, Xiaoming; Chen, Changya; Liao, Hanpeng; Chen, Zhi; Zhou, Shungui
Graphical abstract: Highlights: The molecular changes of DOM during composting are first investigated by FT-ICR MS. The DOM of compost mainly consists of lignins/carboxylic rich alicyclic molecules. The low O/C and high H/C compounds are preferentially decomposed by HTC. Most of organic intermediates are transformed into humic substances during HTC. The contributions of plants and microbes to producing humic substances are explored. Abstract: The aim of this work was to study the molecular compositional changes of dissolved organic matter (DOM) during hyperthermophilic composting (HTC) using electrospray ionization coupled with Fourier transform ion cyclotron resonance mass spectrometry. Our results reveal that DOM in hyperthermophilic compost mainly consisted of lignins/carboxylic-rich alicyclic molecules (72%) with relatively lower H/C (1.24), and the higher double bound equivalent (5.98) and aromaticity index (0.22) when compared with the DOM in composting materials, suggesting that HTC led to an increase in carboxyl-rich, unsaturated, and aromatic compounds. Profiles of the DOM's transformation indicated that low O/C (O/C < 0.3) and high H/C (H/C < 1.5) compounds were preferentially decomposed in the hyperthermophilic phase of HTC. Abundant produced intermediates, such as lignin phenols and amino sugars, were further transformed to refractory humic substances. This investigation extends the current understanding of the molecular mechanisms on humification of HTC, and reveals further applications for hyperthermophilic compost.